Perception of the admitted students to higher education on the development of their communicative competence - Arnao Vásquez, Marcos Oswaldo (2014)
This research allowed knowing what is the perception of students of the first cycle on the level of development of their communicative competences, their discursive processes and capabilities, at the college-going moment to the university and after developing the subject of language and communication I. For this purpose, it was implemented an instrument of survey type in two moments: input and output. The most important result is that the actions performed in this programme allowed to students integrate to their communicative competence new discursive practices of university culture, and develop new processes of reading and writing of the academic one, successfully.